The Effect Of Red Betel Infusion Perineal Care On The Healing Time Of Grade II Perineal Wounds After Delivery - Emi Br Barus (Jurnal EduHealth, 2024)
Most mothers who give birth experience perineal injuries that can cause postpartum infections. The wound healing process is a series of body events that respond to damage to skin integrity through specific stages that overlap. The wound healing phase is divided into four three, namely the inflammatory phase, the proliferation or epithelialization phase, and finally the maturation or remodeling phase. After the three stages are passed, the healing process will occur and the wound tissue will heal as before. The speed or slowness of wound healing time varies for each postpartum mother because it is influenced by other factors that affect. Red betel infusion is known as one of the perineal wound care therapies that is easy to do, cheap, and safe to do, this technique also has an effect on healing perineal wounds and also contains high anti-infection. The study used the Quasy Experiment method with a Nonequivalent Pretest-Posttest Control Group Design research design. Sampling used a non-probability sampling technique with an accidental sampling approach, a sample of 38 was divided into two groups, namely the group given red betel infusion perineal care and the group not given red betel infusion perineal care. Researchers conducted daily wound development assessments on two groups until the wounds healed or for approximately 10 days using the Redness, Edema, Ecchymosis, Discharge, Approximation (REEDA) perineum scale observation sheet. Based on the results of the Mann Whitney test, a p-value of 0.001 was obtained, meaning there was a difference in the administration of red betel leaf infusion perineal care on the healing time of postpartum perineal wounds between the group given red betel leaf infusion and the group not given red betel leaf infusion.